2019
DOI: 10.1117/1.jbo.24.6.066008
|View full text |Cite
|
Sign up to set email alerts
|

Detecting inflammation in rheumatoid arthritis using Fourier transform analysis of dorsal optical transmission images from a pilot study

Abstract: A clinical need exists for low-cost and noninvasive imaging tools capable of detecting inflammation in the joints of inflammatory arthritis patients. Previous studies have reported an optical contrast between inflamed and noninflamed joints resulting from distinct absorption and scattering properties. Accurate classification using nonocclusion-based continuous wave, transillumination imaging was limited to patient-specific changes during follow-up examination as opposed to single time-point examination, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…The three models simulated with the expected changes due to RA produced observable differences in spectral and spatial information. Most notable was the suppression of the spatial peak in transmission near the joint, consistent with the changes in spatial profiles observed in [15]. However, considering the experimentally observed inter-subject variability, a more sensitive indicator might be needed.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The three models simulated with the expected changes due to RA produced observable differences in spectral and spatial information. Most notable was the suppression of the spatial peak in transmission near the joint, consistent with the changes in spatial profiles observed in [15]. However, considering the experimentally observed inter-subject variability, a more sensitive indicator might be needed.…”
Section: Discussionsupporting
confidence: 67%
“…Optical techniques providing both spatial and spectral information are hyperspectral (HSI) [12] and multispectral imaging (MSI) [13,14]. In a pilot study involving 144 joints from 21 rheumatology patients, transmittance images were obtained at five wavelengths (650, 710, 730, 830, and 930 nm) [15]. Accurate detection of inflamed joints was demonstrated, based on Fourier transform analysis of optical transmission images.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a few studies also reported using finger joint models to simulate light transmission through healthy and inflamed joints. Lighter et al [ 32 ] used a simple 2D model of a joint with only four different tissue types, where they attempted to simulate the inflammation as a non-physiologic, circular scattering in the joint cavity. Although simulations resulted in the transmitted light linear profiles roughly resembling their experimental findings, the profiles were featureless, not showing fine joint details.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the author of [36] used the acquisition of optical pictures using a CCD (charge-coupled device) image sensor from the side of the dorsal hand. In order to detect optical modifications, a non-tomographic, single-wavelength, CW transillumer has earlier been provided, in which a light source focused on the finger's side, using a CCD camera sensor to collect the images on the palmar side.…”
Section: Sensors For Detecting Ramentioning
confidence: 99%